Anthropometric Dimensions and Preferred Working Surface Heights for the Electronic Operators Workbench - Mohd Yusof, Rosnah; Haque, Anawarul; Chelven, Muthamil (Universiti Putra Malaysia Press, 1994)
The electronics industry in Malaysia is a leading contributor to the economy, and its contribution will undoubtedly rise in future. Currency it employs more than 168,000 workers and is expected to introduce more new jobs. Ergonomics studies have shown that workplace design greatly influences the performance of workers. Since workbenches are widely used in the electronics industry, design of workbenches with optimal assembly working surface heights for the workers must be considered. A study was conducted to gather data for recommendations for an optimal working surface height for female electronics operators in Malaysia. This paper presents the findings of the above study. Relevant anthropometric dimensions and work surface height preferences for 52 female adults in the Faculty of Engineering, Universiti Pertanian Malaysia, Serdang were recorded. The relationship between preferred work surface height and elbow height was analysed